Gears and God : technocratic fiction, faith, and empire in Mark Twain's America - Williams, Nathaniel, 1970- (Studies in American literary realism and naturalism., 2018)
"A revealing study of the connections between nineteenth-century technological fiction and American religious faith. In this work, Nathaniel Williams analyzes the genre of technology-themed exploration novels--dime novel adventure stories featuring steam-powered and electrified robots, airships, and submersibles. This genre proliferated during the same cultural moment when evolutionary science was dismantling Americans' prevailing, biblically based understanding of human history"--